2021
DOI: 10.2147/rmhp.s308754
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Insufficiency Among University Students: Prevalence, Risk Factors, and the Association Between Vitamin D Deficiency and Episodes of Respiratory Tract Infections

Abstract: Background: Vitamin D deficiency (VDD) and insufficiency (VDI) is a public health problem worldwide. Low blood levels of vitamin D have been associated with many illnesses, including respiratory tract infections (RTIs). This study aims to evaluate the prevalence of VDD and VDI among university students, assess the correlation with demographic and anthropometric factors, and determine the effect of VDD on the respiratory tract infection (RTI) incidence. Methods: A cross-sectional and prospective design was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A recent research study conducted by Saeed et al , thoroughly reviewed and analyzed the impact of vitamin D supplementation on respiratory tract infections. The findings revealed that individuals who were vitamin D deficient and took vitamin D supplements had a reduced likelihood of developing ARTIs (36). However, the study did not investigate how ARTIs affect vitamin D levels.…”
Section: Discussionmentioning
confidence: 92%
“…A recent research study conducted by Saeed et al , thoroughly reviewed and analyzed the impact of vitamin D supplementation on respiratory tract infections. The findings revealed that individuals who were vitamin D deficient and took vitamin D supplements had a reduced likelihood of developing ARTIs (36). However, the study did not investigate how ARTIs affect vitamin D levels.…”
Section: Discussionmentioning
confidence: 92%
“…A possible explanation is that young adults tend to have lower consumption of vitamin D-containing foods such as fortified cereals and oily fish [55], also due to the seasonal variation in sunlight exposure, especially during the winter [54]. Besides dietary intake and sun exposure habits, young adults aged 18-29 often spend increased time indoors due to their attendance in college or graduate school, contributing to a greater prevalence of vitamin D deficiency within this demographic, as documented by multiple studies [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency 2 linked vitamin D deficiency to an increased risk of RTIs. 7 Children with recurrent chest infections had an 84.6% prevalence of vitamin D insufficiency, per the Chandrashekhara T, et alstudy. 8 Vitamin D deficiency is more common in infants who are exclusively breastfed, preterm infants, newborns who do not receive vitamin D supplements, and kids from lower socioeconomic families.…”
Section: Introductionmentioning
confidence: 90%